From prospective historian to the first female leader in Thailand’s international luxury hotel industry - Aumpa, Nopparat; Taweephol, Rachanon; Siriwong, Pitak (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This autoethnographic inquiry investigates the emergence of empowered feminine leadership within Thailand’s international luxury hotel industry through the lived experiences of the researcher—the first Thai woman appointed as general manager in a global hotel chain. Far beyond a personal narrative, this study situates individual experience as a critical lens for interpreting systemic structures, organizational culture, and gendered power relations. Data were constructed through reflective life writing and in-depth interviews with 17 purposively selected key informants. Analysis followed Braun & Clarke’s Thematic Analysis, reinforced by Theory Triangulation drawing from Intersectional Feminism, the Glass Ceiling Theory, and Hofstede’s Cultural Dimensions. The findings are structured into five key themes: (1) the formation of feminine leadership identity under patriarchal constraints; (2) the negotiation of identity within male-dominated hospitality cultures; (3) the transformation of resistance into leadership momentum; (4) emotional dynamics as catalysts for inner empowerment; and (5) the synthesis of the Prismatic Feminine Leadership Model (PRISM)—a fourfold framework comprising Problem Recognition (PRISM), Reframing (Refract), Illuminating Margins (Illuminate), and Systemic Metamorphosis. This model challenges traditional leadership paradigms by proposing a leadership style grounded not in dominance or mimicry of masculine traits, but in quiet strength, emotional intelligence, inclusive systems design, and strategic cultural reframing. Rather than confronting power structures head-on, PRISM advocates for rechanneling perceptions and redirecting organizational optics to recognize alternative leadership forms. This study contributes to feminist leadership theory, transnational service management, and organizational change discourse by offering a structurally rooted, emotionally attuned, and contextually responsive leadership model—one that not only transforms institutions but also opens new entryways for marginalized voices in global service leadership. Article history: Received 2 August 2024 Revised 1 July 2025 Accepted 3 July 2025 SIMILARITY INDEX = 1.96 %